Modern human DNA analyses with special reference to the inner dual-structure model of Yaponesian - Timothy Adrian, Jinam; Yosuke, Kawai; Naruya, Saitou (J-Stage, 2021)
Previous studies suggested two major migration events during the Jomon and Yayoi periods that affected the genetic diversity of modern Japanese (Yaponesians). We explored the possibility of a three-wave migration model by examining three datasets of modern human DNA: (1) whole mitochondrial (mt) DNA genomes of 1642 Yaponesians; (2) mtDNA haplogroup frequencies of 59105 Yaponesians from 47 prefectures; and (3) genome-wide SNP data of two Yaponesians (Ainu, Okinawa) and whole-genome sequence data of Yamato individuals, the Funadomari Jomon F23 individual, and three East Asian populations (Korean, northern Chinese, and southern Chinese). Past population size change was estimated based on dataset 1, and we clearly observed a steep population increase after the Yayoi period. Principal-component analysis and phylogenetic network analysis were applied to dataset 2, and we confirmed the pattern consistent with our model. An admixture program was used on dataset 3, and we found that the two- and three-layer migration models are both compatible with these SNP data. Taken together, these three datasets provide support for our three-wave, ‘inner dual-structure’ model.